Knowledge, attitude and practices of contraception among urban women in Mangaluru, Karnataka - George, Jibi Stephen; Kumar, Hemant (International Journal Of Community Medicine And Public Health, 2019)
Background: India with 50% percent of its population in reproductive age group is the second most populous country in the world with an estimated population of 1.37 billion and if measures are not taken; it is likely to rise to 1.68 billion by the year 2050.The answer lies in promoting small family norms by modern contraceptive methods with the proposed goal of 75% coverage by 2030. In the backdrop of above present research was conceived to study, the knowledge, attitude and practices of contraception among urban women in Mangaluru, Karnataka. Methods: Present study is a cross sectional study. A total of 110 urban women were evaluated with the help of a pre-designed and pre-tested questionnaire for the knowledge, attitude and practices on various prevalent contraceptive methods. Results: Though all the participants were found to be aware of available contraceptives, only 57.3% of them had used one or the other method in their life time. The attitude of large majority (82.7%) of study subjects was found to be positive. The most commonly used contraceptive was condom 73.9%, followed by oral pills (39.2%) and Copper -T (23.9%). Desire for male child (30.1%), lack of awareness (15.1%) and fear of side effects (11.3%) were cited as the main barriers to the use of contraceptives. Conclusions: The study brings out the need for health educational strategies to create awareness in the community on family planning and contraceptive methods.